2022
DOI: 10.1111/myc.13529
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of risk factors and outcome of patients with and without COVID‐19‐associated pulmonary aspergillosis from Pakistan: A case–control study

Abstract: Background Early identification of COVID‐19‐associated pulmonary aspergillosis (CAPA) is particularly challenging in low‐ middle‐income countries where diagnostic capabilities are limited, and risk factors for CAPA have not been identified. It is also essential to recognise CAPA patients who are likely to have a poorer outcome to decide on aggressive management approaches. Therefore, this study aimed to identify risk factors and outcomes for CAPA among admitted moderate to critical COVID‐19 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Permpalung et al found no difference in intensive care unit (ICU) mortality among 39 patients [ 6 ]. A larger cohort identified an association but was limited by unspecified follow-up and single-center design [ 35 ]. An analysis in 20 centers showed higher 90-day ICU mortality in 109 aspergillosis patients and adjusted for immortal time bias [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Permpalung et al found no difference in intensive care unit (ICU) mortality among 39 patients [ 6 ]. A larger cohort identified an association but was limited by unspecified follow-up and single-center design [ 35 ]. An analysis in 20 centers showed higher 90-day ICU mortality in 109 aspergillosis patients and adjusted for immortal time bias [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…• Infectious and bacterial diseases module: This module connects several factors that have a high impact on mortality prediction, including "Diseases of liver", "Other bacterial diseases", "Diseases of the genitourinary system", and "Mycoses". Patients in the ICU are often susceptible to infections, which can worsen their clinical outcomes [51][52][53] ; interactions with liver diseases, which are known to be correlated with mortality themselves 54,55 , have also been reported…”
Section: /20mentioning
confidence: 99%
“…Invasive pulmonary aspergillosis and pulmonary mucormycosis are the most common mould infections and share common risk factors and clinical‐radiological presentation. Besides neutropenia, organ transplantation and haematological malignancies, poorly controlled diabetes mellitus is an important predisposing factor for invasive mould infection in developing countries 1,2 . Both pulmonary mucormycosis and aspergillosis cases significantly increased following the COVID‐19 pandemic in India, especially in those with additional predisposing factors 3–5 .…”
Section: Introductionmentioning
confidence: 99%